Generation of functional human hepatocytes in vitro: current status and future prospects - Tomoko Yamaguchi; Juntaro Matsuzaki; Takeshi Katsuda; Yoshimasa Saito; Hidetsugu Saito; Takahiro Ochiya (Inflammation and Regeneration, 2019)
Abstract Liver and hepatocyte transplantation are the only effective therapies for late-stage liver diseases, in which the liver loses its regenerative capacity. However, there is a shortage of donors. As a potential alternative approach, functional hepatocytes were recently generated from various cell sources. Analysis of drug metabolism in the human liver is important for drug development. Consequently, cells that metabolize drugs similar to human primary hepatocytes are required. This review discusses the current challenges and future perspectives concerning hepatocytes and hepatic progenitor cells that have been reprogrammed from various cell types, focusing on their functions in transplantation models and their ability to metabolize drugs.